2021
DOI: 10.3897/zookeys.1044.63803
|View full text |Cite
|
Sign up to set email alerts
|

What shapes ground beetle assemblages in a tree species-rich subtropical forest?

Abstract: As woody plants provide much of the trophic basis for food webs in forests their species richness, but also stand age and numerous further variables such as vegetation structure, soil properties and elevation can shape assemblages of ground beetles (Coleoptera: Carabidae). However, the combined impact of these numerous variables on ground beetle diversity and community structure has rarely been studied simultaneously. Therefore, ground beetles were studied in 27 plots in a highly diverse and structurally heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…The formation of characteristic assemblages in these two taxonomic groups for the study sites in the research area has been shown in former studies, e.g., Szyszko-Podgórska [33]; Schwerk et al [70]. The sensitive reaction of carabid beetles to soil pH has also been previously reported, e.g., Koivula [25]; Zumstein et al [71]; Nietupski et al [72]. It can also be assumed that many other soil parameters correlate with soil pH [73,74].…”
Section: Carabids and Butterfliessupporting
confidence: 64%
“…The formation of characteristic assemblages in these two taxonomic groups for the study sites in the research area has been shown in former studies, e.g., Szyszko-Podgórska [33]; Schwerk et al [70]. The sensitive reaction of carabid beetles to soil pH has also been previously reported, e.g., Koivula [25]; Zumstein et al [71]; Nietupski et al [72]. It can also be assumed that many other soil parameters correlate with soil pH [73,74].…”
Section: Carabids and Butterfliessupporting
confidence: 64%
“…Lioptera erotyloides is more widely distributed in subtropical East Asia and is also found in the Gutianshan National Park (China). Zumstein et al (2021) were able to detect both this pericaline species and comparably colored erotyloids in flight interception traps there, but we were not able to observe the species alive in the field. However, the parallels shown here between ground beetles and fungus beetles are striking.…”
Section: Natural History-based Sciencementioning
confidence: 71%